PPAR-gamma in overcoming kinase resistance in chronic myeloid leukemia - Yousefi, B; Shafiei-Irannejad, V; Azimi, A; Samadi, N; Zarghami, N (Cellular and Molecular Biology, 2016)
Peroxisome proliferator-activated receptor gamma (PPARÎ³) plays key roles in regulating cellular differentiation, proliferation and apoptosis pathways. As such, they are considered promising targets for anticancer drug development, especially for breast cancer, multiple myeloma and hematologic malignancies. Chronic myeloid leukemia (CML) is a myeloproliferative disorder arising from an oncogenic Bcr-Abl tyrosine kinase. Inhibitors of this oncogene by small molecules such as imatinib are effective only in 75% of the patient’s population. One of the potential strategies to overcome this resistance is to devise combination therapy protocols with other therapeutic agents including PPAR ligands. Since PPAR ligands are potentially interesting in different hematologic malignancies, this article will review the potential of PPAR ligands for use in CML treatment.